Adsorption behavior of engineered carbons and carbon nanomaterials for metal endocrine disruptors: Experiments and theoretical calculation. (May 2019) - Zhang, Chen; Wang, Wenjun; Duan, Abing; Zeng, Guangming; Huang, Danlian; Lai, Cui; Tan, Xiaofei; Cheng, Min; Wang, Rongzhong; Zhou, Chengyun; Xiong, Weiping; Yang, Yang
Abstract: Adsorption behaviors and mechanisms of metal endocrine disruptors (Pb 2+, Cd 2+, and Hg 2+ ) by pyrogenic carbonaceous materials including engineered carbons (biochar and activated carbon) and carbon nanomaterials (multi-walled carbon nanotubes and graphene oxide) have been investigated by experimental and density functional theory (DFT) studies. The adsorption isotherms of metal endocrine disruptors on carbonaceous materials were better fitted by Langmuir models. The adsorption capacities were in the order as follows: GO > BC600 > BC300 > CNT > AC for Pb 2+, GO > BC300 > AC > BC600 > CNT for Cd 2+, and GO > BC300 ≥ AC > CNT > BC600 for Hg 2+, respectively. The DFT-computed binding energy (kcal/mol) of different oxygen-containing functional groups with metal endocrine disruptors followed the orders: (ⅰ) CMCOCPb (−136.70) > CM-COO - -Pb (−91.58) > CMCOPb (−33.57) > CMOHPb (−4.69), (ⅱ) CM-COO - -Cd (−45.91) > CMCOCCd (−4.49) > CMOHCd (−3.68) > CMCOCd (1.08), (ⅲ) CM-COO - -Hg (−25.51) > CMCOCHg (−3.58) > CMOHHg (−0.63) > CMCOHg (0.23). And COC has the highest binding energy for Pb 2+, whereas COC has much lower binding energy for Cd 2+ and Hg 2+ . Comprehensively considering DFT calculations, competitive adsorption results and the cost analysis, this work may provide insights into the design of selective adsorbent for specific contaminant. Graphical abstract: Image 1 Highlights: Adsorption capacity of the adsorbents for metal endocrine disruptors was compared. DFT calculation was used to study the effect of oxygen-containing groups. COO - has the highest binding energy for Cd 2+ and Hg 2+ . COC has the highest binding energy for Pb 2+, followed by COO - . Biochar was found suitable for large scale environmental remediation.